PENGARUH MEDIA PEMBELAJARAN AUDIO VISUAL TERHADAP KEMAMPUAN BERBICARA ANAK KELOMPOK B DI PAUD TERPADU TERATAI UNM MAKASSAR - Miftahul Jannah; Uswatun Hasanah (Universitas Muhammadiyah Jakarta, 2019)
Audio visual learning media is a form of stimulation that can be given to improve children's development, especially the development of children. This study aims to find out the description of children's speaking ability using audio visual media, to find out the description of children's speaking ability with the Conversional method, and to determine the effect of the use of audio-visual learning media on the speaking skills of Group B children in Teratai UNM Makassar Kindergarten. This research design uses Quasi Experiment or quasi-experimental. while the sample of the study was group B2 with 11 children for the experimental group and group B1 with 11 children for the control group. Data collection techniques through test, observation and documentation techniques. The data analysis technique used was descriptive statistical analysis and nonparametric statistical analysis. This study shows that there is a significant difference in the development of children's speaking with conventional methods using audio-visual media. As for the calculated T value that is 66 and T table 11 then the results obtained T count (66)> T table (11) H1 is accepted and Ho is rejected means that there is an influence of audio-visual learning media on children's speaking ability. While the calculated Z value obtained is 2.93 and 1.645 Z table, the results obtained Z count (2.93)> Z table (1.645) H1 is accepted and Ho is rejected which means that there is an influence of audio-visual learning media on children's speaking ability. The results of this study indicate that the speaking ability of children receiving treatment in the form of audiovisual media is better than before being given treatment. So it can be concluded that the use of audio-visual learning media influences the speaking ability of Group B children in Teratai UNM Makassar Kindergarten.